Behavioural effects in mice orally exposed to domoic acid or ibotenic acid are influenced by developmental stages and sex differences - Sasaki, Takahiro; Saito, Hirokatsu; Hiradate, Yuuki; Hara, Kenshiro; Tanemura, Kentaro (Biochemical and biophysical research communications, 2021)
The structure of the brain is dramatically altered during the critical period. Physiological substances (neurotransmitters, hormones, etc.) in the body fluctuate significantly before and after sexual maturation. Therefore, the effect of chemical exposure on the central nervous system often differs depending on the developmental stage and sex. We aimed to compare the behavioural effects that emerged from the administration of chemicals to mice of different life stages (immature or mature) and different sex (male or female). We administered mice with domoic acid (DA), a marine poison, and ibotenic acid (IA), found in poisonous mushrooms. These excitatory amino acids act as agonists for glutamate and are potent neurotoxins. Interestingly, the behavioural effects of these chemicals were completely different. Following DA administration, we observed memory deficits only in groups of male mice treated at maturity. Following IA administration, we observed deviations in emotional behaviour in groups of male mice treated at both immaturity and maturity. In contrast, few characteristic changes were detected in all groups of females. Our results support the theory that the behavioural effects of chemical administration vary considerably with developmental stages and sex. In conclusion, our findings promote better understanding of individual differences in excitatory chemical-induced neurotoxicity and provide evidence for future risk strategies and treatments. •・Domoic acid (DA) and ibotenic acid (IA) are potent neurotoxins.•・As glutamate agonists, DA and IA exposure cause varied behavioural effects.•・Behavioural effects of DA and IA are based on developmental stages and sex.•・Different behavioural effects of DA and IA are based on the timing of administration.•・The resistance to DA and IA was higher in female mice, indicating sex differences.